2018
DOI: 10.1002/eap.1760
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary evolution and scaling of 32 major cities in China

Abstract: Most of the planet's population currently lives in urban areas, and urban land expansion is one of the most dramatic forms of land conversion. Understanding how cities evolve temporally, spatially, and organizationally in a rapidly urbanizing world is critical for sustainable development. However, few studies have examined the coevolution of urban attributes in time and space simultaneously and the adequacy of power law scaling across cities and through time, particularly in countries that have experienced abr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 66 publications
(143 reference statements)
3
31
0
Order By: Relevance
“…The result (10) also suggests that if F ext > 0 and b i > 1, which means that both the intercept parameter (global growth) and the population are growing in time, then β i will always be greater than the global exponent β T . The increment in the intercept implies a more accentuated slope of the city trajectory in the plane ln Y-x-ln N (that is, bigger β i ) in relation to the transversal trajectory (related to β T ), in accordance with empirical observations brought by our study as well as other evidences available in recent literature [49][50][51]. To sum up, the transversal and longitudinal scaling exponent will only be the same when:…”
Section: Plos Onesupporting
confidence: 91%
See 2 more Smart Citations
“…The result (10) also suggests that if F ext > 0 and b i > 1, which means that both the intercept parameter (global growth) and the population are growing in time, then β i will always be greater than the global exponent β T . The increment in the intercept implies a more accentuated slope of the city trajectory in the plane ln Y-x-ln N (that is, bigger β i ) in relation to the transversal trajectory (related to β T ), in accordance with empirical observations brought by our study as well as other evidences available in recent literature [49][50][51]. To sum up, the transversal and longitudinal scaling exponent will only be the same when:…”
Section: Plos Onesupporting
confidence: 91%
“…In short, does an individual city growing in time follow the same scaling pattern observed for a snapshot of a group of cities? In the last years, few works have accurately focused on the dynamics of individual cities [47][48][49][50][51], while a growing literature has been concentrating on the scaling properties of sets of cities. We call the former longitudinal scaling properties, which take into account the evolution of individual cities in time, and the latter transversal scaling across an urban system, i.e., computed from the set of cities that compose the system.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Combining them, we could get the third metric population per unit area, which contains information on population density. Furthermore, GDP per unit of urban land area was used to present land use efficiency of wealth creation [34,35]. We ranked these four indicators to explore the differences among cities and intraurban agglomeration dynamics.…”
Section: The Evolution Of Urban Rank Sizementioning
confidence: 99%
“…Ci ty-size distribution (CD) has consistently remained a topic of interest in urban geography and economics [1][2][3]. Since Auerbach [4] found that CD followed a Pareto distribution in 1913, an increasing number of scholars have focused on the analysis of this rule [5,6].…”
Section: Introductionmentioning
confidence: 99%